Chronic exposure to aluminum, nickel, thallium and uranium and their relationship with essential elements in human whole blood and blood serum - Zeneli, Lulzim; Sekovanić, Ankica; Daci, Nexhat (Journal of environmental science and health. Part A, Toxic/hazardous substances & environmental engineering, 2015)
This study aimed to evaluate the influence of exposure to aluminum, nickel, thallium and uranium on the metabolism of essential elements in humans, as well as the relationship between uranium, thallium, nickel, and aluminum and essential elements (Ca, Mg, Zn, Se, Mn, Co, Cr, and Mo) in the whole blood and blood serum of healthy men who were occupationally exposed. This study included 97 healthy men, 31-64 years age, including 70 workers in a thermo power plant and 27 control subjects. The results showed that chronic, moderate exposure of trace elements (Al, Ni, Tl, and U) lead to decreased serum chromium (SCr) and blood molybdenum levels (BMo), whereas by the results achieved in terms of correlations between non-essential and essential elements, non-essential elements such as uranium, thallium, nickel, and aluminum, despite their concentration within the reference values, are strongly competitive with essential elements in biochemical processes.